Positive electrode material, composite positive electrode material, positive electrode plate, preparation methods of positive electrode material and positive electrode plate, and lithium ion power battery
By using nickel-cobalt-manganese ternary material and lithium manganese phosphate in the positive electrode material of lithium-ion power batteries, and doping M elements and A elements to form a composite positive electrode material, the bottlenecks in energy density and service life of power lithium-ion batteries are solved, and battery performance with high energy density, long life and high safety is achieved.
Patent Information
- Application Number
- CN202411994519.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-12-31
AI Technical Summary
Existing powered lithium-ion batteries have bottlenecks in terms of energy density and service life, especially inadequate safety in charging and discharging under extreme conditions.
A positive electrode material mainly consisting of nickel-cobalt-manganese ternary material and lithium manganese iron phosphate are used, and M elements and A elements are doped to form a composite positive electrode material. This material improves cycling performance and safety by forming strong M-O bonds and improving ionic conductivity, stabilizing the crystal structure, suppressing phase transitions and Li/Ni mixing.
It significantly improves the energy density and circulation performance of lithium-ion power batteries, improves safety performance, and extends the battery life.
Smart Images

Figure CN119786576A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of battery materials, and relates to a positive electrode material, a composite positive electrode material, a positive electrode sheet and a preparation method thereof, and a lithium-ion power battery. Background Art
[0002] In recent years, as the new energy market continues to develop and mature, users have increasingly strong requirements for high vehicle endurance, so there is an urgent need for power lithium-ion batteries with higher energy density to meet market needs. At the same time, the use scenarios of new energy vehicles are becoming more and more diverse, and the environment and conditions faced by power batteries are becoming more and more severe, such as high and low temperature discharge, circulation and storage, which puts higher requirements on the service life of lithium-ion batteries. In addition, retired power lithium-ion batteries from new energy vehicles can be reused in logistics vehicles, base stations, communications and building backup power supplies through cascade utilization, so it is also necessary to further improve the service life of lithium-ion batteries.
[0003] However, the most mainstream power lithium-ion battery in the industry is still lithium iron phosphate battery, with a general energy density of 160-180Wh / kg. A few battery factories with strong R&D capabilities can increase the energy density to more than 190Wh / kg. But in the final analysis, even if the influence of negative electrode materials, current collectors, binders, conductive agents, electrolytes, etc. in the battery is excluded, it is difficult to achieve the ultimate target of lithium iron phosphate (≥200Wh / kg). In addition, another common positive electrode material for power batteries is ternary materials. Although this material has higher energy density, better high-rate charge and discharge performance and low-temperature performance, its cycle performance is not as good as lithium iron phosphate, and its safety performance is poor and the cost is high, which is not conducive to the further development of enterprises and new energy industries. When the battery is used for a long time under harsh conditions, the by-products will accumulate and block the pores of the pole pieces and diaphragms due to the shrinkage and expansion of the pole pieces, and the presence of various electrolyte-related side reactions inside the battery cells, which will cause the negative electrode SEI film to be damaged and thickened, accompanied by gas production, etc., and eventually the battery cell cycle will jump, lithium precipitation and various failures, which will affect the actual energy density and service life of the power battery.
[0004] In order to improve the energy density and service life of power batteries, a common method is to solve the problem through lithium supplementation technology. For example, lithium supplementation through slurry, that is, metallic lithium or organic matter containing lithium, modified materials, etc., main materials and non-aqueous liquids are mixed into slurry, and coated on the current collector to make pole pieces. Although this method can improve the energy density of lithium-ion batteries, metallic lithium has high reactivity and is very easy to react with oxygen and moisture in the air, and the process is too difficult. Alternatively, lithium-rich lithium salts, lithium oxides, lithium-containing organic matter and other materials are used to supplement lithium at the positive electrode, but due to the activity of lithium supplementation materials and utilization issues, there are great difficulties in actual application. In addition, in order to improve the safety of batteries, most battery factories achieve the purpose of fast heat dissipation, short circuit prevention and pressure relief by optimizing battery diaphragms, electrolytes, etc. and structural size design methods, thereby reducing the risk of thermal runaway of batteries to a certain extent, but it does not fundamentally solve the safety of charging and discharging of lithium batteries under extreme conditions, which involves the intrinsic safety and thermal stability of positive electrode materials.
[0005] In view of this, the present invention is proposed. Summary of the invention
[0006] In view of the bottlenecks encountered in further significantly improving the energy density of the iron-lithium system in the current power battery field and reducing the impact of internal side reaction products of the battery on the energy density and service life, the present invention aims to provide a positive electrode material, a composite positive electrode material, a positive electrode plate and a preparation method and a lithium-ion power battery.
[0007] In order to achieve the above purpose, the following technical solutions are adopted:
[0008] The first object of the present invention is to provide a positive electrode material for a lithium-ion power battery, the general formula of the positive electrode material is:
[0009] Li 2 (Ni a Co b Mn c ) 1-d M d O 2 ·Mn x Fe y PO 4 A;
[0010] Wherein, a+b+c=1, and 0<a≤0.6, 0<b≤0.1, 0<c<0.4, 0<d≤0.01, M is selected from at least one of Cu, Al, W, Ti, Sr, Sb, Nb, Mg, Zr, Zn, La, Y, S, N, B or F;
[0011] x+y=1, and 0<x<1, 0<y<1, x:y=(0.2~0.8):(0.8~0.2); A is selected from at least one of Mg, Zn, Cu, Co, Ni, Cr, V, Ti, Zr or C elements.
[0012] Further, based on the above technical solution of the present invention, the particle size of the positive electrode material is 5 to 30 μm;
[0013] And / or, the specific surface area of the positive electrode material is 1 to 40 m 2 / g;
[0014] And / or, the positive electrode material is made of a nickel-cobalt-manganese ternary material precursor, a lithium iron manganese phosphate precursor, a first dopant containing an M element, and a second dopant containing an A element;
[0015] The second object of the present invention is to provide a method for preparing the above-mentioned positive electrode material, which is prepared by the following method 1 or method 2:
[0016] Method 1: Mix the nickel-cobalt-manganese ternary material precursor and the lithium iron manganese phosphate precursor in proportion to obtain a composite precursor;
[0017] Adding a first dopant containing an M element and a second dopant containing an A element to a composite precursor, and then sintering to obtain a positive electrode material; or,
[0018] Method 2: adding a first dopant containing the M element during the preparation of a nickel-cobalt-manganese ternary material precursor to obtain a nickel-cobalt-manganese ternary material precursor doped with the M element;
[0019] In the process of preparing the lithium iron manganese phosphate precursor, a second dopant containing the element A is added to obtain the lithium iron manganese phosphate precursor doped with the element A;
[0020] The nickel-cobalt-manganese ternary material precursor doped with the M element and the lithium manganese iron phosphate precursor doped with the A element are mixed in proportion and then sintered to obtain a positive electrode material.
[0021] Further, on the basis of the above technical solution of the present invention, in method 1, the particle size of the nickel-cobalt-manganese ternary material precursor is 1 to 15 μm; and / or the particle size of the lithium iron manganese phosphate precursor is 100 to 400 nm;
[0022] And / or, in method 1, the mass ratio of the nickel-cobalt-manganese ternary material precursor to the lithium iron manganese phosphate precursor is (0.2-0.8):(0.8-0.2);
[0023] And / or, in method 1, the mass fraction of the first dopant in the composite precursor is 1-2%;
[0024] And / or, in method 1, the mass ratio of the first dopant to the second dopant is (0.2-0.8):(0.8-0.2);
[0025] And / or, in method 2, the mass ratio of the nickel-cobalt-manganese ternary material precursor doped with element M to the lithium iron manganese phosphate precursor doped with element A is (0.2-0.8): (0.8-0.2);
[0026] And / or, in method 2, the mass fraction of the first dopant in the nickel-cobalt-manganese ternary material precursor is 2-3%;
[0027] And / or, in method 2, the mass fraction of the second dopant in the lithium manganese iron phosphate precursor is 1-3%;
[0028] And / or, in method 1 and method 2, the sintering temperature is 600-800° C., the sintering time is 3-12 hours, and the sintering atmosphere is nitrogen or helium.
[0029] The third object of the present invention is to provide a composite positive electrode material for a lithium-ion power battery, comprising the positive electrode material provided by the first object of the present invention and a coating layer coated on the surface of the positive electrode material;
[0030] The coating layer is mainly made of a composite additive, and the composite additive includes at least two substances selected from bis(fluorosulfonyl)imide lithium salt, 2-allylphenoxytrimethylsilane, Lewis base or a compound containing N / B elements.
[0031] Further, based on the above technical solution of the present invention, the thickness of the coating layer is 5 to 50 nm;
[0032] And / or, the mass ratio of the composite additive to the positive electrode material is (1-50):100, preferably (5-20):100;
[0033] And / or, the Lewis base includes at least one of N-dimethylamide and N-acetylcaprolactam;
[0034] And / or, the N / B element-containing compound includes a N element-containing compound and / or a B element-containing compound, the N element-containing compound includes a nitrile compound and / or an amine compound, and the B element-containing compound includes a boric acid ester compound and / or a borane compound.
[0035] The fourth object of the present invention is to provide a method for preparing a composite positive electrode material, comprising the following steps: physically blending the composite additive and the positive electrode material, and then drying to obtain the composite positive electrode material.
[0036] A fifth object of the present invention is to provide a positive electrode plate, comprising a current collector and a positive electrode material layer formed on the surface of the current collector;
[0037] The positive electrode material layer includes: a conductive agent, a binder, and the positive electrode material provided by the first purpose of the present invention or the composite positive electrode material provided by the third purpose of the present invention.
[0038] The sixth object of the present invention is to provide a method for preparing a positive electrode sheet, which is prepared by the following method 1, method 2 or method 3:
[0039] Method 1: Prepare the conductive agent, the binder and the positive electrode material or the composite positive electrode material into a slurry, apply it on the surface of the current collector, and dry it to obtain a positive electrode sheet;
[0040] Method 2: The positive electrode material, composite additive, conductive agent and binder are made into slurry, coated on the surface of the current collector, and dried to obtain a positive electrode sheet;
[0041] Method three: The positive electrode material, the conductive agent and the binder are made into a slurry, which is coated on the surface of the current collector, and then the composite additive is sprayed on the surface of the positive electrode material layer of the current collector, and dried to obtain a positive electrode sheet.
[0042] The seventh object of the present invention is to provide a lithium-ion power battery, comprising the positive electrode material provided by the first object of the present invention or the composite positive electrode material provided by the third object of the present invention or the positive electrode plate provided by the fifth object of the present invention.
[0043] Compared with the prior art, the technical solution of the present invention has at least the following technical effects:
[0044] (1) The present invention provides a positive electrode material for lithium-ion power batteries, wherein the chemical composition of the positive electrode material is mainly based on nickel-cobalt-manganese ternary material and lithium iron manganese phosphate, and is doped with M element and A element. The main function of M element is to stabilize the crystal structure by forming a strong MO bond, reduce the generation of oxygen vacancies, inhibit phase transformation and Li / Ni mixing, and promote Li + Migration; The main function of element A is to improve the ionic conductivity and diffusion performance of the material from the inside of the lattice, and can inhibit the Jan-Taylor effect. This cathode material combines the advantages of both ternary and lithium manganese iron phosphate, integrating high specific capacity of 220-280mAh / g, high cycle stability and high safety, improving the dual voltage platform, thereby significantly improving the energy density, and significantly improving the cycle performance and safety performance compared to ternary materials.
[0045] (2) The present invention also provides a composite positive electrode material for a lithium-ion power battery, comprising the above-mentioned positive electrode material provided by the present invention and a coating layer coated on the surface of the positive electrode material, wherein the coating layer is mainly made of a specific type of composite additive; wherein the composite additive can form a nanoscale interface protection film (coating layer) on the surface of the positive electrode material particles, and its main component does not chemically react with the electrolyte. During the actual charging and discharging process of the battery, it will preferentially react with HF produced by oxidative decomposition of the electrolyte, and transfer F ions to the high-fluorine interface film, which not only eliminates HF in the electrolyte, but also improves the stability of the interface film, while inhibiting the dissolution of transition metal ions and reducing the generation of by-products, thereby significantly improving the cycle performance of the high-energy density composite positive electrode material. BRIEF DESCRIPTION OF THE DRAWINGS
[0046] Figure 1 A schematic diagram of the preparation process of the composite precursor provided by the present invention;
[0047] Figure 2 A schematic diagram of the process for preparing the positive electrode material provided by the present invention;
[0048] Figure 3 Schematic diagram of the preparation process of the composite positive electrode material provided by the present invention. DETAILED DESCRIPTION
[0049] In order to make the purpose, technical scheme and advantages of the present invention clearer, the technical scheme in the embodiment of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present invention. The process parameters of the following embodiments that do not specify specific conditions are usually based on conventional conditions.
[0050] The endpoints and any values of the ranges disclosed in the present invention are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be regarded as specifically disclosed in the present invention.
[0051] According to a first aspect of the present invention, a positive electrode material for a lithium-ion power battery is provided, the general formula of the positive electrode material is:
[0052] Li 2 (Ni a Co b Mn c) 1-d M d O 2 ·Mn x Fe y PO 4 A;
[0053] Wherein, a+b+c=1, and 0<a≤0.6, 0<b≤0.1, 0<c<0.4, 0<d≤0.01, M is selected from at least one of Cu, Al, W, Ti, Sr, Sb, Nb, Mg, Zr, Zn, La, Y, S, N, B or F;
[0054] x+y=1, and 0<x<1, 0<y<1, x:y=(0.2~0.8):(0.8~0.2); A is selected from at least one of the elements Mg, Zn, Cu, Co, Ni, Cr, V, Ti, Zr or C.
[0055] The chemical composition of the positive electrode material is mainly based on nickel-cobalt-manganese ternary material and lithium manganese iron phosphate, and is doped with M element and A element. Among them, M element is mainly doped or coated in the ternary material, mainly in the form of high-valent metal ions or non-metallic ions. Its main function is to stabilize the crystal structure by forming a strong MO bond, reduce the generation of oxygen vacancies, inhibit phase transformation and Li / Ni mixing, and promote Li + Migration; A element is mainly doped or coated in lithium manganese iron phosphate, mainly in the form of metal ions or non-metallic elements C. Its main function is to improve the ionic conductivity and diffusion performance of the material from the inside of the lattice, and can inhibit the Jan-Taylor effect. The C coating element can improve the electronic conductivity of the material and reduce side reactions with the electrolyte. This positive electrode material combines the advantages of ternary and lithium manganese iron phosphate, integrates high specific capacity of 220-280mAh / g, high cycle stability and high safety, improves the dual voltage platform, and thus significantly improves the energy density. Compared with ternary materials, it can significantly improve the cycle performance and safety performance. It should be noted that although the M element is mainly doped or coated in the ternary material, and the A element is mainly doped or coated in the lithium manganese iron phosphate, there may be some M elements that may be doped or coated in the lithium manganese iron phosphate, and some A elements may be doped or coated in the ternary material. This situation has little effect on the comprehensive performance of the positive electrode material, because the M element and the A element as dopants can penetrate each other in the composite precursor, thereby having a mutual synergistic gain effect in the positive electrode material.
[0056] In the general formula, b represents the content of the Co element. Limiting it to a specific numerical range is mainly to improve the energy density of the material while taking into account the stability and safety of the material cycle. The typical but non-restrictive values of b are 0.01, 0.02, 0.04, 0.05, 0.06, 0.08 or 0.1, etc.; d represents the content of the doped or coated M element. Limiting it to a specific numerical range can improve the electrical conductivity and kinetic properties of the material while ensuring the material performance. The typical but non-restrictive values of d are 0.002, 0.005, 0.008 or 0.01, etc. In addition, limiting the ratio range between x and y is conducive to the preparation of precursors or materials of lithium manganese iron phosphate with different performance characteristics. It is adjusted according to actual needs. The typical but non-restrictive x:y is 0.2:0.8, 0.3:0.7, 0.4:0.6, 0.5:0.5, 0.6:0.4, 0.7:0.3 or 0.8:0.2, etc.
[0057] As an optional embodiment of the present invention, the particle size of the positive electrode material is 5 to 30 μm, and typical but non-limiting particle sizes are 5 μm, 10 μm, 15 μm, 20 μm, 25 μm or 30 μm, etc., and the numerical range between any two points.
[0058] As an optional embodiment of the present invention, in the general formula of the positive electrode material, M is selected from at least one of the elements Nb, Al, B or F, and A is selected from at least one of the elements Mg, Cu or C.
[0059] As an optional embodiment of the present invention, the positive electrode material is made of a nickel-cobalt-manganese ternary material precursor, a lithium iron manganese phosphate precursor, a first dopant containing an M element, and a second dopant containing an A element.
[0060] As an optional embodiment of the present invention, the specific surface area of the positive electrode material is 1 to 40 m 2 / g, for example, 1m 2 / g, 5m 2 / g, 10m 2 / g, 20m 2 / g, 30m 2 / g or 40m 2 / g, etc.
[0061] There is no specific limitation on the preparation method of the nickel-cobalt-manganese ternary material precursor and the lithium iron manganese phosphate precursor, and they can be prepared by conventional chemical preparation methods or physical preparation methods in the art. Chemical preparation methods include but are not limited to high-temperature solid phase method, carbon thermal reduction method, hydrothermal method, coprecipitation method, pulsed laser deposition method synthesis, sol-gel method, etc. Physical preparation methods include but are not limited to high-energy ball milling, physical vapor deposition method and high-speed mixing method, etc.
[0062] In the preparation process of nickel-cobalt-manganese ternary material precursor and lithium iron manganese phosphate precursor, the lithium sources selected include Li 2 CO 3 、LiOH、Li 2 O、CH 3 COOLi、LiNO 3 and Li 2 C 2 O 4 One or more of; the nickel source, manganese source and cobalt source in the ternary material are, for example, nickel sulfate, manganese sulfate and cobalt sulfate; the manganese source in lithium manganese iron phosphate includes one or more of manganese sulfate, manganese carbonate or manganese hydroxide, and the iron source includes FePO 4 , Fe 2 O 3 , FeOOH, Fe(OH) 3 、Fe(NO 3 ) 3 , Fe 2 (SO 4 ) 3 One or more of .
[0063] As an optional embodiment of the present invention, the particle size of the nickel-cobalt-manganese ternary material precursor is 1 to 15 μm, and the typical but non-limiting particle size is 1 μm, 2 μm, 5 μm, 8 μm, 10 μm, 12 μm or 15 μm, etc., and the numerical range between any two points.
[0064] As an optional embodiment of the present invention, the particle size of the lithium manganese iron phosphate precursor is 100-400 nm, and the typical but non-limiting particle size is 100 nm, 150 nm, 200 nm, 250 nm, 300 nm, 350 nm or 400 nm, and the numerical range between any two points.
[0065] As an optional embodiment of the present invention, the first dopant is mainly used to provide the M element. When the M element is a metal element, the raw material form of the first dopant can be a cation-containing (Cu 2+ , Nb 5+ Mg 2+ 、Zn 2+ ,La 3+ , B 3+ , Y 3+ etc.) compounds, such as phosphates, acetates, nitrates, etc., or metal oxides (Al 2 O 3 、ZrO 2 , WO 3 、TiO 2 etc.); M is a non-metallic element (F - , S 2- When it is a sulfide, a fluoride, etc., it can be a sulfide, a fluoride, etc.
[0066] As an optional embodiment of the present invention, the second dopant is mainly used to provide element A, and A is selected from Mg 2+ 、Zn 2+ , Cu 2+ 、Co 3+ 、Ni 2+ Cr 3+ 、V 3+ 、Ti 4+ 、Zr 4+ When the A element is a metal element, the raw material form of the second dopant may be a cation-containing (Mg 2+ 、Zn 2+ , Cu 2+ 、Ni 2+ Cr 3+ etc.) compounds, such as phosphates, acetates, nitrates, etc., or metal oxides (Co 2 O 3 、ZrO 2 、V 2 O 3 、TiO 2 When M is a non-metallic element C, its raw material can be in the form of sugars, such as glucose, sucrose, starch, etc., or an organic polymer, such as polyvinyl alcohol (PVA), polyethylene glycol, polyvinyl alcohol, etc., or a small molecule organic substance, such as citric acid, oxalic acid, vitamin C, etc.
[0067] According to a second aspect of the present invention, a method for preparing the positive electrode material provided in the first aspect of the present invention is also provided, which is prepared by the following method 1 or method 2:
[0068] Method 1: Mixing a nickel-cobalt-manganese ternary material precursor (NCM precursor) and a lithium manganese iron phosphate precursor (LMFP precursor) in proportion to obtain a composite precursor;
[0069] A first dopant containing an M element and a second dopant containing an A element are added to the composite precursor, and then sintered to obtain a positive electrode material. The preparation process diagram is shown in FIG. Figure 1 and Figure 2 as shown; or
[0070] Method 2: adding a first dopant containing the M element during the preparation of a nickel-cobalt-manganese ternary material precursor to obtain a nickel-cobalt-manganese ternary material precursor doped with the M element;
[0071] In the process of preparing the lithium iron manganese phosphate precursor, a second dopant containing the element A is added to obtain the lithium iron manganese phosphate precursor doped with the element A;
[0072] The nickel-cobalt-manganese ternary material precursor doped with the M element and the lithium manganese iron phosphate precursor doped with the A element are mixed in proportion and then sintered to obtain a positive electrode material.
[0073] The first dopant (corresponding to the M element) and the second dopant (corresponding to the A element) can be added during the sintering process of the composite precursor. This method has a simple synthesis process, high production efficiency and low cost.
[0074] The first dopant (corresponding to the M element) and the second dopant (corresponding to the A element) can also be added before sintering, that is, when synthesizing the precursor. The chemical methods used to synthesize the precursor include conventional solid-phase method or liquid-phase method. The solid-phase method uses high-temperature solid-phase reaction method, carbon thermal reduction method, microwave synthesis method, etc.; the liquid-phase method is sol-gel method, hydrothermal synthesis method, etc. This method makes the doping and coating efficiency high, the uniformity good, and the structure and performance stable.
[0075] As an optional embodiment of the present invention, in method one, the mass ratio of the nickel-cobalt-manganese ternary material precursor and the lithium iron manganese phosphate precursor is (0.2-0.8): (0.8-0.2); a typical but non-limiting mass ratio is 0.2:0.8, 0.3:0.7, 0.4:0.6, 0.5:0.5, 0.6:0.4, 0.7:0.3 or 0.8:0.2, etc.
[0076] The relative amount of the first dopant and the second dopant is determined according to the ratio of the nickel-cobalt-manganese ternary material precursor to the lithium iron manganese phosphate precursor. As an optional embodiment of the present invention, the mass ratio of the first dopant to the second dopant is (0.2-0.8): (0.8-0.2). For example, the mass ratio of the first dopant to the second dopant is 0.2:0.8, 0.3:0.7, 0.4:0.6, 0.6:0.4, 0.7:0.3 or 0.8:0.2, etc.
[0077] As a preferred embodiment of the present invention, in method 1, the mass fraction of the first dopant in the composite precursor (nickel-cobalt-manganese ternary material precursor and lithium manganese iron phosphate precursor) is 1-2%, for example, 1%, 1.2%, 1.5%, 1.6%, 1.8% or 2%, etc.; and / or,
[0078] The mass fraction of the second dopant in the composite precursor (nickel-cobalt-manganese ternary material precursor and lithium iron manganese phosphate precursor) is 0.5-2%, for example, 0.5%, 0.75%, 1%, 1.2%, 1.5%, 1.6%, 1.8% or 2%.
[0079] As an optional embodiment of the present invention, in method 2, the mass ratio of the nickel-cobalt-manganese ternary material precursor doped with element M and the lithium iron manganese phosphate precursor doped with element A is (0.2-0.8):(0.8-0.2), for example, 0.2:0.8, 0.3:0.7, 0.4:0.6, 0.5:0.5, 0.6:0.4, 0.7:0.3 or 0.8:0.2, etc.
[0080] As an optional embodiment of the present invention, in method 2, the mass fraction of the first dopant in the nickel-cobalt-manganese ternary material precursor is 2-3%, for example, 2%, 2.2%, 2.4%, 2.5%, 2.6%, 2.8% or 3%, etc.; and / or,
[0081] In method 2, the mass fraction of the second dopant in the lithium manganese iron phosphate precursor is 1-3%, for example, 1%, 1.2%, 1.4%, 1.5%, 1.6%, 1.8%, 2%, 2.2%, 2.4%, 2.5%, 2.6%, 2.8% or 3%.
[0082] As an optional embodiment of the present invention, in method 1 and method 2, the sintering temperature is 600-800°C, and the sintering time is 3-12h. Typical but non-limiting sintering temperatures are 600°C, 650°C, 700°C, 750°C or 800°C, and the numerical range between any two points, and typical but non-limiting sintering times are 3h, 4h, 5h, 6h, 8h, 10h or 12h, and the numerical range between any two points.
[0083] As an optional embodiment of the present invention, in method one and method two, the sintering atmosphere is nitrogen or helium.
[0084] According to a third aspect of the present invention, there is provided a composite positive electrode material for a lithium-ion power battery, comprising the positive electrode material provided by the first aspect of the present invention and a coating layer coated on the surface of the positive electrode material;
[0085] The coating layer is mainly made of a composite additive, and the composite additive includes at least two substances selected from lithium bis(fluorosulfonyl)imide (LiFSI), 2-allylphenoxytrimethylsilane, Lewis base or a compound containing N / B elements.
[0086] An appropriate amount of lithium bis(fluorosulfonyl)imide salt is beneficial to improving the ionic conductivity of the material in the electrolyte. In addition, it can enhance the thermal stability and electrochemical window of the composite additive, improve the interfacial film performance, inhibit HF generation, and improve the cycle, rate and safety.
[0087] 2-Allylphenoxytrimethylsilane can effectively form a complex with HF in the electrolyte and preferentially form an interfacial protective film on the positive electrode surface compared to ester solvents, allowing F ions to transfer into the interfacial film while improving the stability of the interfacial film.
[0088] Lewis bases such as amide additives (e.g. N-acetyl caprolactam) can react with PF 5 , HF or H 2 O has a strong complexing effect.
[0089] The " / " in the compound containing N / B element means "and / or", that is, it can be a compound containing N element, it can be a compound containing B element, or it can contain both compounds containing N element and compounds containing B element. The compound containing N element can adjust the solvation structure of ions in the electrolyte, so that the Li ions can be transmitted more smoothly in the electrolyte, and can participate in the formation of solid electrolyte membrane on the electrode surface during the charge and discharge process to reduce side reactions; the compound containing B element can stabilize the electrode structure, adjust the interface chemical properties, inhibit the formation of HF and improve the high temperature performance.
[0090] The composite additive can form a nanoscale interface protection film (coating layer) on the surface of the positive electrode material particles. Its main component does not react chemically with the electrolyte. During the actual charging and discharging process of the battery, it will preferentially react with the HF produced by the oxidative decomposition of the electrolyte, and transfer the F ions to the high-fluorine interface film, which not only eliminates the HF in the electrolyte, but also improves the stability of the interface film. At the same time, it inhibits the dissolution of transition metal ions (mainly from synthetic positive electrode materials, such as Ni ions, Co ions, Mn ions in ternary materials and Mn ions in lithium manganese iron phosphate), reduces the generation of by-products, and significantly improves the cycle performance of high-energy density composite positive electrode materials.
[0091] The composite additive can continuously consume the HF in the electrolyte and inhibit the generation of by-products, which improves the stability of the SEI film at the negative electrode interface to a certain extent, while reducing the accumulation of by-products in the late cycle and thus clogging the pores.
[0092] As a preferred embodiment of the present invention, the composite additive includes lithium bis(fluorosulfonyl)imide and 2-allylphenoxytrimethylsilane, on which Lewis base or compounds containing N / B elements (inorganic salts) may be added.
[0093] The composite additive can form a nano-scale fluorine-containing protective film on the surface of the positive electrode material. Because it contains a certain lithium salt component in the electrolyte, it can also charge the positive electrode active material during the use of the battery, thereby increasing the energy density of the power battery and extending its life.
[0094] As an optional embodiment of the present invention, the coating layer has a thickness of 5 to 50 nm. Typical but non-limiting coating layer thicknesses are 5 nm, 8 nm, 10 nm, 15 nm, 20 nm, 25 nm, 30 nm, 35 nm, 40 nm, 45 nm or 50 nm.
[0095] As an optional embodiment of the present invention, the mass ratio of the composite additive to the positive electrode material is (1-50):100, preferably (5-20):100.
[0096] The mass ratio of the composite additive to the positive electrode material should not be too high. When it is higher than 50:100, the properties of the interface film (SEI, CEI) will deteriorate, the electrode reaction will be disturbed, the gas production problem will be aggravated, and the cost will increase. Therefore, the typical but non-restrictive mass ratio of the composite additive to the positive electrode material is 1:100, 5:100, 10:100, 12:100, 15:100, 18:100, 20:100, 22:100, 25:100, 30:100, 35:100, 40:100, 45:100 or 50:100, etc.
[0097] By further limiting the mass ratio of the composite additive to the positive electrode material and limiting it within a fixed numerical range, it is beneficial to give full play to the electrical properties and interface stability of the composite positive electrode material and reduce costs.
[0098] As an optional embodiment of the present invention, the Lewis base includes at least one of N-dimethylamide and N-acetylcaprolactam.
[0099] As an optional embodiment of the present invention, the compound containing N / B element includes a compound containing N element and / or a compound containing B element. Among them, the compound containing N element includes a nitrile compound (such as adiponitrile, etc.) or an amine compound (such as triethylamine, etc.). The compound containing B element includes a boric acid ester compound (such as boric acid ester, etc.) and / or a borane compound.
[0100] According to a fourth aspect of the present invention, a method for preparing the composite positive electrode material is also provided, comprising the following steps: physically blending the composite additive and the positive electrode material, and then drying them to form a powder to obtain the composite positive electrode material.
[0101] In order to improve the uniformity of the positive electrode material and the composite additive, wet blending can be used. In addition, in addition to directly using the above-mentioned physical blending method to prepare the composite positive electrode material, the composite additive can also be added during the preparation of the positive electrode slurry, and the slurry can be coated on the current collector, or the composite additive can be sprayed on the electrode sheet coated with the positive electrode active material with a thickness of micrometers, so as to form a coating layer made of the composite additive on the surface of the positive electrode material. The preparation diagram is shown in FIG. Figure 3 shown.
[0102] According to a fifth aspect of the present invention, there is also provided a positive electrode sheet, comprising a current collector and a positive electrode material layer formed on a surface of the current collector;
[0103] The positive electrode material layer includes a conductive agent, a binder and the positive electrode material provided in the first aspect of the present invention or the composite positive electrode material provided in the third aspect of the present invention.
[0104] In view of the advantages brought by the above-mentioned positive electrode materials or composite positive electrode materials, the positive electrode sheet containing them has the same advantages.
[0105] According to a sixth aspect of the present invention, there is also provided a method for preparing the positive electrode sheet according to the fifth aspect of the present invention, which is prepared by the following method 1, method 2 or method 3:
[0106] Method 1: Prepare a slurry of a conductive agent, a binder and a positive electrode material or a composite positive electrode material, apply it on the surface of a current collector, and dry it to obtain a positive electrode sheet;
[0107] Method 2: The positive electrode material, composite additive, conductive agent and binder are made into slurry, coated on the surface of the current collector, and dried to obtain a positive electrode sheet;
[0108] Method three: The positive electrode material, conductive agent and binder are made into a slurry, coated on the surface of the current collector, dried, and then the composite additive is sprayed on the surface of the positive electrode material layer of the current collector, and dried again to obtain the positive electrode sheet.
[0109] The above preparation methods can all achieve stable preparation of positive electrode sheets.
[0110] As an optional embodiment of the present invention, when performing method 3, the spraying method includes spraying, screen printing and scraping, etc. The spraying thickness is 0.5-10 μm, for example, 0.5 μm, 1 μm, 2 μm, 4 μm, 5 μm, 6 μm, 8 μm, 9 μm or 10 μm, etc.
[0111] According to a seventh aspect of the present invention, there is also provided a lithium-ion power battery comprising the above-mentioned positive electrode material, composite positive electrode material or positive electrode plate.
[0112] In view of the advantages of the above-mentioned positive electrode material, composite positive electrode material or positive electrode plate of the present invention, the compaction density, specific capacity, cycle performance and safety performance of the lithium-ion power battery containing the same are maintained at a good level.
[0113] As an optional embodiment of the present invention, the lithium-ion power battery includes a battery case, a top cover, a pole core and an electrolyte, etc. The electrolyte and the pole core are sealed in the battery case, the pole core adopts a winding or lamination process, and the pole core includes a positive electrode, a negative electrode and a separator located between the positive electrode and the negative electrode, and the positive electrode includes a positive electrode current collector and a positive electrode material layer located on the positive electrode current collector and mainly made of a positive electrode material or a composite positive electrode material.
[0114] The present invention will be further described in detail below with reference to specific embodiments and comparative examples.
[0115] Example 1
[0116] This embodiment provides a positive electrode material, the general formula of which is:
[0117] Li 2 (Ni a Co b Mn c ) 1-d M d O 2 ·Mn x Fe y PO 4 A;
[0118] Where a = 0.6, b = 0.1, c = 0.3, d = 0.01, M is the element Nb, with Nb 5+ Existing in ionic form; x = 0.6, y = 0.4, A is C (carbon coating),
[0119] That is, the positive electrode material is Li 2 (Ni 0.6 Co 0.1 Mn 0.3 ) 0.99 Nb 0.01 O 2 ·Mn 0.6 Fe 0.4 PO 4 ·C.
[0120] The method for preparing the positive electrode material of this embodiment comprises the following steps:
[0121] The nickel-cobalt-manganese ternary material precursor (particle size 3-5 μm) and the lithium manganese iron phosphate precursor (particle size 100-200 nm) were mixed at a mass ratio of 0.6:0.4, and the first dopant (NbCl 5 ) and a second dopant (glucose), the mass fraction of the first dopant in the nickel-cobalt-manganese ternary material precursor is 2.5±0.5%, the mass ratio of the first dopant to the second dopant is 0.6:0.4, and then sintered at 690-710°C in a helium atmosphere for 10 hours to obtain a positive electrode material.
[0122] The nickel-cobalt-manganese ternary material precursor is prepared by a coprecipitation method, which includes the following steps:
[0123] Nickel sulfate, manganese sulfate and cobalt sulfate were added to deionized water to prepare a mixed solution, wherein the molar ratio of Ni, Co and Mn in the mixed solution was 0.6:0.1:0.3, ammonia water (0.4 mol / L) and sodium hydroxide aqueous solution (1 mol / L) were introduced into the mixed solution, the pH of the reaction system was adjusted to 11.5, and the reaction was carried out at 40±2°C and 580 rpm with stirring. During the reaction, nitrogen gas was introduced as a protective gas for protection. After the reaction was completed, the solid product was washed with deionized water and dried at 100°C to obtain the ternary material precursor Ni 0.6 Co 0.1 Mn 0.3 (OH) 2 .
[0124] The preparation method of lithium manganese iron phosphate precursor comprises the following steps:
[0125] A manganese source (manganese carbonate), an iron source (iron phosphate), ammonium hydrogen phosphate and a lithium salt (lithium carbonate) are mixed, the molar ratio of manganese carbonate, iron phosphate, ammonium hydrogen phosphate and lithium carbonate is 60%:40%:100%:50%, the mixing frequency of the high-speed mixer is 50 Hz, and the mixing time is 30 minutes to obtain a manganese iron phosphate lithium precursor.
[0126] Example 2
[0127] This embodiment provides a positive electrode material, the general formula of which is:
[0128] Li 2 (Ni a Co b Mn c ) 1-d M d O 2 ·Mn x Fe y PO 4 A;
[0129] Where a = 0.55, b = 0.1, c = 0.35, d = 0.01, M is Al, Al 3+ Exists in ionic form; x=0.7, y=0.3, A is Mg, Mg 2+ Exists in ionic form;
[0130] That is, the positive electrode material is Li 2 (Ni 0.55 Co 0.1 Mn 0.35 ) 0.99 Al0.01 O 2 ·Mn 0.7 Fe 0.3 PO 4 Mg.
[0131] The method for preparing the positive electrode material of this embodiment comprises the following steps:
[0132] The nickel-cobalt-manganese ternary material precursor (particle size 3-5 μm) and the lithium manganese iron phosphate precursor (particle size 100-200 nm) were mixed at a mass ratio of 0.7:0.3, and the first dopant (Al 2 O 3 ) and the second dopant (Mg(NO 3 ) 2 ), the mass fraction of the first dopant in the nickel-cobalt-manganese ternary material precursor is 2.5±0.5%, the mass ratio of the first dopant to the second dopant is 0.7:0.3, and then sintering is carried out at 790-710°C for 10 hours in a helium atmosphere to obtain a positive electrode material.
[0133] Example 3
[0134] This embodiment provides a positive electrode material, the general formula of which is:
[0135] Li 2 (Ni a Co b Mn c ) 1-d M d O 2 ·Mn x Fe y PO 4 A;
[0136] Among them, a=0.5,b=0.1,c=0.4,d=0.01,M is B,B 3+ Exists in the form of; x = 0.8, y = 0.2, A is Cu, Cu 2+ Form exists;
[0137] That is, the positive electrode material is Li 2 (Ni 0.5 Co 0.1 Mn 0.4 ) 0.99 B 0.01 O 2 ·Mn 0.8 Fe 0.2 PO 4 ·Cu.
[0138] The method for preparing the positive electrode material of this embodiment comprises the following steps:
[0139] The nickel-cobalt-manganese ternary material precursor (particle size 3-5 μm) and the lithium manganese iron phosphate precursor (particle size 100-200 nm) are mixed at a mass ratio of 0.4:0.6, and the first dopant (B 2 O 3 ) and the second dopant (Cu(NO 3 ) 2 ), the mass fraction of the first dopant in the nickel-cobalt-manganese ternary material precursor is 2.5±0.5%, the mass ratio of the first dopant to the second dopant is 0.4:0.6, and then sintering is carried out at 690-710°C for 10 hours in a helium atmosphere to obtain a positive electrode material.
[0140] Example 4
[0141] This embodiment provides a composite positive electrode material, comprising the positive electrode material provided in Embodiment 1 and a coating layer coated on the surface of the positive electrode material;
[0142] The coating layer is mainly made of composite additives, and the thickness of the coating layer is 20±5nm. The composite additives include lithium bis(fluorosulfonyl)imide (LiFSI) and 2-allylphenoxytrimethylsilane (APTS), and the mass ratio of lithium bis(fluorosulfonyl)imide to 2-allylphenoxytrimethylsilane is 0.6:0.4.
[0143] The method for preparing the composite positive electrode material of this embodiment comprises the following steps:
[0144] The positive electrode material and the composite additive are mixed in a mass ratio of 100:10, and then dried to form a powder to obtain a composite positive electrode material.
[0145] Example 5
[0146] This embodiment provides a composite positive electrode material, except that the composition of the composite additive is adjusted, that is, the composite additive includes lithium bis(fluorosulfonyl)imide (LiFSI), 2-allylphenoxytrimethylsilane (APTS) and Lewis base (N-acetylcaprolactam), the mass ratio of lithium bis(fluorosulfonyl)imide, 2-allylphenoxytrimethylsilane and Lewis base is 0.3:0.5:0.2, and the remaining raw material ratios and preparation methods are the same as those in Example 4.
[0147] Example 6
[0148] This embodiment provides a composite positive electrode material, except that the composition of the composite additive is adjusted, that is, the composite additive includes lithium bis(fluorosulfonyl)imide (LiFSI) and Lewis base (N-acetylcaprolactam), the mass ratio of lithium bis(fluorosulfonyl)imide and Lewis base is 0.6:0.4, and the remaining raw material ratios and preparation methods are the same as those in Example 4.
[0149] Example 7
[0150] This embodiment provides a method for preparing a composite positive electrode material. In addition to mixing the positive electrode material and the composite additive in a mass ratio of 100:15, the thickness of the coating layer formed by the composite additive on the surface of the positive electrode material is 20±5nm, and the specific composition of the remaining composite additives is the same as that in Example 4.
[0151] Example 8
[0152] This embodiment provides a composite positive electrode material, comprising the positive electrode material provided in Embodiment 2 and a coating layer coated on the surface of the positive electrode material;
[0153] The coating layer is mainly made of composite additives, and the coating layer thickness is 20±5nm. The composite additives include 2-allylphenoxytrimethylsilane (APTS) and a compound containing N element (adiponitrile), and the mass ratio of 2-allylphenoxytrimethylsilane to the compound containing N element is 0.3:0.7.
[0154] The method for preparing the composite positive electrode material of this embodiment comprises the following steps:
[0155] The positive electrode material and the composite additive are mixed in a mass ratio of 100:13, and then dried to form a powder to obtain a composite positive electrode material.
[0156] Example 9
[0157] This embodiment provides a composite positive electrode material, comprising the positive electrode material provided in Embodiment 3 and a coating layer coated on the surface of the positive electrode material;
[0158] The coating layer is mainly made of composite additives, and the thickness of the coating layer is 20±5nm. The composite additives include lithium bis(fluorosulfonyl)imide (LiFSI) and 2-allylphenoxytrimethylsilane (APTS), and the mass ratio of lithium bis(fluorosulfonyl)imide to 2-allylphenoxytrimethylsilane is 0.4:0.6.
[0159] The method for preparing the composite positive electrode material of this embodiment comprises the following steps:
[0160] The positive electrode material and the composite additive are mixed in a mass ratio of 100:12, and then dried to form a powder to obtain a composite positive electrode material.
[0161] Comparative Example 1
[0162] This comparative example provides a positive electrode material, the general formula of which is:
[0163] Li 1 (Ni a Co b Mn c ) 1-d Md O 2 ;
[0164] Where a = 0.6, b = 0.1, c = 0.3, d = 0.01, M is the element Nb, with Nb 5+ Ionic form; that is, the positive electrode material is Li(Ni 0.6 Co 0.1 Mn 0.3 ) 0.99 M 0.01 O 2 .
[0165] The preparation method of the positive electrode material of this comparative example comprises the following steps:
[0166] The nickel-cobalt-manganese ternary material precursor (particle size 3-5 μm) and the first dopant (NbCl 5 ) are mixed, the mass fraction of the first dopant in the nickel-cobalt-manganese ternary material precursor is 2.5±0.5%, and then sintered at 690-710° C. for 10 h in a helium atmosphere to obtain a positive electrode material.
[0167] The preparation method of the nickel-cobalt-manganese ternary material precursor is the same as that in Example 1.
[0168] Comparative Example 2
[0169] This comparative example provides a positive electrode material, the general formula of which is:
[0170] LiMn x Fe y PO 4 A;
[0171] Wherein, x=0.6, y=0.4, A is C (carbon coating layer), that is, the positive electrode material is LiMn 0.6 Fe 0.4 PO 4 ·C.
[0172] The preparation method of the positive electrode material of this comparative example comprises the following steps:
[0173] A lithium iron manganese phosphate precursor (particle size 100-200nm) and a second dopant (glucose) were mixed, the mass fraction of the second dopant in the lithium iron manganese phosphate precursor being 1.5±0.5%, and then sintered at 690-710°C for 10 hours in a helium atmosphere to obtain a positive electrode material.
[0174] The preparation method of the lithium manganese iron phosphate precursor is the same as that in Example 1.
[0175] Comparative Example 3
[0176] This comparative example provides a composite positive electrode material. Except for adjusting the composition of the composite additive in Example 4, that is, only using lithium bis(fluorosulfonyl)imide (LiFSI) as an additive to coat the positive electrode material, the remaining raw material ratios and preparation methods are the same as those in Example 4.
[0177] Comparative Example 4
[0178] This comparative example provides a composite positive electrode material. Except for adjusting the composition of the composite additive in Example 4, that is, only using 2-allylphenoxytrimethylsilane (APTS) as an additive to coat the positive electrode material, the remaining raw material ratios and preparation methods are the same as those in Example 4.
[0179] In order to better illustrate the technical effects of each embodiment and comparative example, the following experimental examples are specially set up.
[0180] Experimental Example 1
[0181] The positive electrode materials or composite positive electrodes prepared in each embodiment and comparative example are made into a power square battery. The lithium-ion power battery includes a battery shell, a pole core and an electrolyte, and the pole core and the electrolyte are sealed in the battery shell; the pole core includes a positive electrode sheet, a negative electrode sheet and a separator located between the positive electrode sheet and the negative electrode sheet, and the positive electrode includes a positive electrode collector and a positive electrode material located on the positive electrode collector. The positive electrode material is the positive electrode material provided in each embodiment and comparative example of the present invention, and the negative electrode material includes a negative electrode collector and a negative electrode material located on the negative electrode collector. The specific preparation method of the battery is as follows:
[0182] Preparation of positive electrode sheet: The positive electrode material, conductive agent (SP and CNT, the mass ratio of SP and CNT is 0.6:0.4), binder (PVDF) and solvent (NMP) prepared in each embodiment or comparative example are mixed, wherein the mass percentage of positive electrode active material, conductive agent and binder is 97.5%:1%:1.5%, and mixed for 3 to 5 hours by a planetary mixer or other high-speed mixer to prepare a positive electrode slurry, and the positive electrode slurry is coated on a 12 to 13 μm aluminum foil by transfer or extrusion coating. The roller compaction density is selected according to the characteristics of each positive electrode main material. Appropriate value (see Table 1 for details) to obtain a positive electrode sheet;
[0183] Preparation of negative electrode sheet: The negative electrode uses conventional artificial graphite as the negative electrode material, and is matched with a conductive agent (SP), a dispersant (CMC), a binder (SBR) and solvent water to make a slurry, wherein the mass percentage of the negative electrode active material, the conductive agent, the dispersant and the binder is 96.5%:1.0%:1.1%:1.5%. The slurry is coated on a 4.5μm or 6μm copper foil in the same coating method as the positive electrode, and then rolled after drying, with a compaction density of 1.56-1.62g / m 3 , to make a negative electrode sheet;
[0184] Diaphragm: PE base film 7μm, single-sided (usually positive electrode side) ceramic layer 2μm, double-sided glue coating 1.5μm each. The purpose of gluing is to make the pole piece and the diaphragm fit more closely during hot pressing, and to increase the overall safety of the battery;
[0185] Electrolyte: 1M LiPF 6 +EC / DEC (1:1 v / v);
[0186] Battery assembly: The positive electrode sheet, negative electrode sheet and separator are put together into a core through a winding machine or a stacking machine, put into a shell, packaged, injected with electrolyte, etc., and finally prepared into a lithium-ion power battery.
[0187] The compaction density, specific capacity, cycle performance and safety of the lithium-ion power battery made of the positive electrode material or composite positive electrode prepared in each embodiment and comparative example were tested. The specific testing method is as follows:
[0188] (1) Compaction density test method: During the rolling process, a small disc is taken from the electrode, weighed, and the thickness of the disc is measured using the calculation formula: PD = (small disc mass - foil mass) / small disc area / (small disc thickness - foil thickness);
[0189] (2) Specific capacity measurement method: The finished battery is subjected to a 1 / 3C discharge capacity test, specifically: 1 / 3C constant current charging to 3.65V, constant voltage 0.05C cut-off, standing for 30 minutes, 1 / 3C constant current discharge to 2.5V; at the same time, the mass of the positive electrode active material contained in all the positive electrode sheets in a single battery cell is calculated, specific capacity = battery cell discharge capacity / mass of positive electrode active material in a single battery cell;
[0190] (3) Cycle test: At 25°C, the battery is properly installed on the Xinwei or Landian battery test cabinet and the same step charge (average 2.2C) and 1C discharge test steps are used for cycle test. Specifically, step charge (average 2.2C) to 3.65V, stand for 30 minutes, then discharge at 1C to 2.5V, stand for 30 minutes, and repeat the cycle. When the battery capacity drops to 80% SOH, it is the end of life.
[0191] (4) Safety Testing
[0192] Needle puncture test: first fully charge the battery cell, then use a 5-8mm high-temperature resistant steel needle to penetrate the battery perpendicular to the wide surface at a speed of 25±5mm / s. The steel needle stays in the battery and is observed for 1 hour. Record whether there is expansion, leakage, smoke, fire or explosion.
[0193] Thermal runaway test: Use a 600W power heating plate to heat the finished battery. When the thermal runaway judgment condition is triggered, stop heating;
[0194] Thermal runaway judgment conditions: When a) and c) or b) and c) occur, it is judged as thermal runaway;
[0195] a) The trigger object generates a voltage drop, and the drop value exceeds 25% of the initial voltage;
[0196] b) The temperature at the monitoring point reaches the maximum operating temperature specified by the manufacturer;
[0197] c) The temperature rise rate dT / dt of the monitoring point is ≥1℃ / s and lasts for more than 3s;
[0198] Observe for 1 hour and record any swelling, leakage, smoking, fire or explosion.
[0199] The specific test results are shown in Table 1.
[0200] Table 1
[0201]
[0202]
[0203] From the data in the above table, we can see that compared with single ternary materials or lithium manganese iron phosphate materials, the compaction density, specific capacity and cycle performance of the positive electrode materials prepared by the composite precursor are at the middle level of the performance of the two materials, but the overall performance of the former two is significantly improved compared with lithium manganese iron phosphate, and the cycle performance and safety are significantly improved compared with ternary materials. Therefore, the advantages of ternary materials and lithium manganese iron phosphate materials are combined, and the overall performance is better.
[0204] In addition, with the addition of composite additives, the cycle performance of the positive electrode material prepared by the composite precursor is further improved to ≥2000 cycles, and a certain amount of different types of additives, and composite additives of different compositions and ratios all have a certain gain effect on the cycle performance of the positive electrode material.
[0205] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention are within the scope of protection of the pending claims of the present invention.
Claims
1. A positive electrode material for a lithium-ion power battery, characterized in that: The general formula of the positive electrode material is: Li2(Ni a Co b Mr c ) 1-d M d O2·Mn x Feb y PO4·A; Wherein, a+b+c=1, and 0<a≤0.6, 0<b≤0.1, 0<c<0.4, 0<d≤0.01, M is selected from at least one of Cu, Al, W, Ti, Sr, Sb, Nb, Mg, Zr, Zn, La, Y, S, N, B or F; x+y=1, and 0<x<1, 0<y<1, x:y=(0.2~0.8):(0.8~0.2); A is selected from at least one of Mg, Zn, Cu, Co, Ni, Cr, V, Ti, Zr or C elements.
2. The positive electrode material according to claim 1, characterized in that In the general formula of the positive electrode material, M is selected from at least one of Nb, Al, B or F elements, and / or A is selected from at least one of Mg, Cu or C elements; And / or, the particle size of the positive electrode material is 5 to 30 μm; And / or, the specific surface area of the positive electrode material is 1 to 40 m 2 / g; And / or, the positive electrode material is made of a nickel-cobalt-manganese ternary material precursor, a lithium iron manganese phosphate precursor, a first dopant containing an M element, and a second dopant containing an A element.
3. The method for preparing the positive electrode material according to claim 1 or 2, characterized in that: Prepared by the following method 1 or method 2: Method 1: Mix the nickel-cobalt-manganese ternary material precursor and the lithium iron manganese phosphate precursor in proportion to obtain a composite precursor; Adding a first dopant containing an M element and a second dopant containing an A element to a composite precursor, and then sintering to obtain a positive electrode material; or, Method 2: adding a first dopant containing the M element during the preparation of a nickel-cobalt-manganese ternary material precursor to obtain a nickel-cobalt-manganese ternary material precursor doped with the M element; In the process of preparing the lithium iron manganese phosphate precursor, a second dopant containing the element A is added to obtain the lithium iron manganese phosphate precursor doped with the element A; The nickel-cobalt-manganese ternary material precursor doped with the M element and the lithium manganese iron phosphate precursor doped with the A element are mixed in proportion and then sintered to obtain a positive electrode material.
4. The method for preparing the positive electrode material according to claim 3, characterized in that: In method 1, the particle size of the nickel-cobalt-manganese ternary material precursor is 1 to 15 μm; and / or the particle size of the lithium manganese iron phosphate precursor is 100 to 400 nm; And / or, in method 1, the mass ratio of the nickel-cobalt-manganese ternary material precursor to the lithium iron manganese phosphate precursor is (0.2-0.8):(0.8-0.2); And / or, in method 1, the mass fraction of the first dopant in the composite precursor is 1-2%; And / or, in method 1, the mass ratio of the first dopant to the second dopant is (0.2-0.8):(0.8-0.2); And / or, in method 2, the mass ratio of the nickel-cobalt-manganese ternary material precursor doped with element M to the lithium iron manganese phosphate precursor doped with element A is (0.2-0.8):(0.8-0.2); And / or, in method 2, the mass fraction of the first dopant in the nickel-cobalt-manganese ternary material precursor is 2-3%; And / or, in method 2, the mass fraction of the second dopant in the lithium manganese iron phosphate precursor is 1 to 3%; And / or, in method 1 and method 2, the sintering temperature is 600-800° C., the sintering time is 3-12 hours, and the sintering atmosphere is nitrogen or helium.
5. A composite positive electrode material, characterized in that: Comprising the positive electrode material according to claim 1 or 2 or the positive electrode material prepared by the preparation method according to claim 3 or 4, and a coating layer coated on the surface of the positive electrode material; The coating layer is mainly made of a composite additive, and the composite additive includes at least two substances selected from bis(fluorosulfonyl)imide lithium salt, 2-allylphenoxytrimethylsilane, Lewis base or a compound containing N / B elements.
6. The composite positive electrode material according to claim 5, characterized in that: The coating layer has a thickness of 5 to 50 nm; And / or, the mass ratio of the composite additive to the positive electrode material is (1-50):100, preferably (5-20):100; And / or, the Lewis base includes at least one of N-dimethylamide and N-acetylcaprolactam; And / or, the N / B element-containing compound includes a N element-containing compound and / or a B element-containing compound, the N element-containing compound includes a nitrile compound and / or an amine compound, and the B element-containing compound includes a boric acid ester compound and / or a borane compound.
7. The method for preparing the composite positive electrode material according to claim 5 or 6, characterized in that: The method comprises the following steps: physically blending the composite additive and the positive electrode material, and then drying to obtain the composite positive electrode material.
8. A positive electrode sheet, characterized in that: It includes a current collector and a positive electrode material layer formed on the surface of the current collector; The positive electrode material layer comprises: a conductive agent, a binder, and the positive electrode material according to any one of claims 1 or 2 or the composite positive electrode material according to claim 5 or 6.
9. The method for preparing the positive electrode sheet according to claim 8, characterized in that: Prepared by the following method 1, method 2 or method 3: Method 1: Prepare a slurry of a conductive agent, a binder and the positive electrode material or a composite positive electrode material, apply it on the surface of a current collector, and dry it to obtain a positive electrode sheet; Method 2: The positive electrode material, composite additive, conductive agent and binder are made into slurry, coated on the surface of the current collector, and dried to obtain a positive electrode sheet; Method three: The positive electrode material, conductive agent and binder are made into a slurry, coated on the surface of the current collector to form a positive electrode material layer, and then the composite additive is sprayed on the surface of the positive electrode material layer and dried to obtain a positive electrode sheet.
10. A lithium-ion power battery, characterized in that it comprises the positive electrode material according to claim 1 or 2, the composite positive electrode material according to claim 5 or 6, or the positive electrode sheet according to claim 8.
Citation Information
Patent Citations
Mixed positive electrode material, positive plate using the same, and lithium ion battery
CN104300123A
Simple, convenient and efficient boron oxide coated high-nickel ternary positive electrode material and preparation method thereof
CN110729466A
High-nickel ternary positive electrode material and preparation method thereof
CN111244397A
Surface coating modified nickel-cobalt-manganese ternary material as well as preparation method and application thereof
CN114497494A
Surface-modified ternary positive electrode material as well as preparation method and application thereof
CN115360345A
Cited By
Lithium manganese iron phosphate-nickel cobalt manganese system semi-solid battery and preparation method thereof
CN122091690A